О формах международного сотрудничества Санкт-Петербургского государственного университета в области экологического образования - Ionov Victor V. (Baltijskij Region, 2016)
The authors analyse different forms of environmental education projects and programmes implemented in the Baltic Sea region. The first one is “The Baltic University” programme taught in English. The “Baltic University” is a network of more than 200 universities from 14 counties of the Baltic Sea region. This education programme offers an opportunity for students to enroll on bachelor and master degree programmes related to environmental and social problems of the Baltic Sea region. The Polar and Marine Sciences, POMOR master programme, represents the second form of international environmental education. Russian and German researchers from six universities and four research centres have developed the programme. The target group of the programme are Russian and international students, studying together during the whole duration of the programme. It is the first internationally accredited MA programme taught in English. International accreditation proves the compliance of the programme with international education standards. The same cooperation model is used in a new international master programme — Cold Regions Environmental Landscapes Integrated Science (CORELIS). The programme started in 2016. It is implemented jointly by Hamburg university (the lead partner of the project), and university professors from Helsinki (Finland) and Lisbon (Portugal). Researchers from the Austrian National Institute of Polar Research (Austria, and Lund University (Sweden) will join the programme at a later stage. Such an approach will help achieve the synergy of the European and Russian approaches to environmental education. The Russian-Norwegian master programme “Geoecological monitoring and rational use of natural resources in the Northern oil and gas production regions” is a good example of the third form of international environmental education. The programme similar to POMOR and CORELIS. However, it has one distinctive feature — Russian and foreign students study together from the second term only. The authors describe the ways of achieving the learning objectives of these master programmes depending on the students’ language skills and their basic knowledge of ecology and nature management.